Canine cerebellar protoplasmic astrocytoma: clinical, histopathological and immunohistochemical features - Silva, Elisângela O. da; Reis, Antônio C. F. dos; Bracarense, Ana Paula F. R. L. (Brazilian Journal of Veterinary Pathology, 2010)
Protoplasmic astrocytomas are uncommon in humans and animals. A 14-year-old, intact female German Shepherd dog presented with a history of ataxia of the pelvic limbs, left-side head torsion and hypermetric response of the right side for approximately 15 days. Neurological examination revealed the presence of cerebellar syndrome and paradoxical vestibular syndrome. Medical therapy was initiated, but neurological signs were progressive, and the owner opted for euthanasia. Gross examination showed no cerebellar lesion. Microscopic features were characterized by prominent background microcystic degeneration and the presence of spindle cells with scant cytoplasm and delicate glial fibers. The immunohistochemical assay showed positive staining for GFAP (glial fibrillar acidic protein), vimentin and S100, and negative staining for factor VIII. A definitive diagnosis of protoplasmic astrocytoma was made on the basis of the histological and immunohistochemical findings.